Inelegibilidade decorrente da rejeição de contas de gestores públicos e a nova interpretação da súmula n. 01 do Tribunal Superior Eleitoral - Morais, George Ventura (2008)
The dissertation was about the ineligibility resulting from rejection of accounts of public representatives and the new interpretation of the Court Orientation nº 01 of the Superior Electoral Court. Although this Court Orientation has not been revoked, it was tried to demonstrate that its most recent interpretation is in the direction of the mitigation of the presumption of innocence, in conformity with the principle of administrative morality, as well as with the fundamental right and fourth generation guarantee of having honest and truthful delegates. The study justified and understood the reasons that correctly made the Court substitute the imperative condition of a desconstitutive judicial demand, combined with the concession of an emergency law order, aiming to reverse the effects of the ineligibility, allowing the deputy, who had his accounts disapproved by uncontested decision of the competent judicial court based on incurable irregularities, to run for office. Through detailed analysis of opening line g of incise I of the first article of Complementary Law nº 64/90, that legally substantiates the suspension of the subjective right of being voted, it was intended to explain controversial questions on the necessary basis for an appropriate handling of the proper judicial measure to impugnate the candidate registration, under the penalty of preclusion. This judicial instrument was approached so that from the pronouncement of the Electoral Court could be withdrawn the most effectiveness expected from it, especially to exclude from an election anyone who does not have the minimal ethical values to represent society, proving that the feeling of purification of the elections reflects straightly the coherent position adopted by the Specialized Court